Analisis Akad Ijarah Muntahiah Bi At Tamlik Dalam Praktik Perbankan Syariah - Nilatus Salamah; Miftahur rahman (Indonesia, 2022)
IMBT is a form of multi-contract product. At the beginning of the contract agreement used by both parties is an ijarah agreement so that there is a transfer of the right to use the benefits from the lessor (Mu'jir/muajir) to the lessee (Musta'jir) accompanied by the transfer of property rights from mu'jir to muajir on the basis of promise. The ijrah contract with ownership at the end is a contract that has been recognized by the Indonesian Ulema Council through the DSN. In Islamic banking, the application of ijarah and IMBT products, the bank works as an investor/provider of funds and promises. This paper aims to find out how IMBT is in Islamic Banking. This study uses a type of library research (library research). Data collection techniques were carried out by means of documentation studies and triangulation. The data analysis technique was carried out by content analysis using a qualitative study with a conceptual realm. The results of the study show that if there is a dispute between the parties, the settlement guideline is an "Unnamed" agreement whose form and submission is based on the agreement of the parties based on article 1338 (1) of the Civil Code; All agreements legally made apply as law to those made.